The Role of Brain Plasticity in Early Childhood Language Learning: A Literature Review for Early Childhood Educators - Aprinalistria, Aprinalistria (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Recent developments in neuroscience have deepened scholarly understanding of brain plasticity and its contribution to early childhood development, especially in relation to language acquisition. Early childhood is widely recognized as a sensitive developmental stage in which the brain exhibits a high level of plasticity, enabling neural structures associated with language to form and adapt rapidly in response to environmental input. Contemporary research highlights the significance of early language exposure, meaningful social interaction, and supportive learning environments in shaping neural pathways that facilitate children’s linguistic growth. Nevertheless, although the body of evidence is expanding, there remains limited clarity regarding the specific neuroplastic processes that underlie language learning in early childhood and how these scientific insights can be translated into practical strategies for educators.The present study aims to synthesize recent scholarly findings on the role of brain plasticity in early childhood language learning and explore their relevance for early childhood education practice. To achieve this objective, a systematic literature review will be conducted using major academic databases such as PubMed and Scopus. The review will include peer-reviewed studies published from the beginning that focus on brain plasticity, early childhood, and language development in early childhood contexts. Articles will be initially screened based on titles, abstracts, and keywords, followed by a full-text assessment to determine eligibility. Selected studies will then be evaluated in terms of methodological rigor and thematic relevance, and data extraction will be carried out independently to enhance reliability.The results of this review are expected to provide updated perspectives on how brain plasticity contributes to language development in early childhood and to offer practical insights that may assist educators in designing more effective language learning experiences for young children.